Pengungkapan Manajemen Risiko, Pengungkapan Modal Intelektual dan Nilai Perusahaan Farmasi - Listiani, Vebyeta; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 31 No 9 (2021), 2021)
Firm value can be interpreted as the expectation of shareholder’s investment value as a reaction to the information conveyed by the company. The value of public company will be reflected in the price of shares traded on the capital market. This study aims to determine the effect of enterprise risk management (ERM) disclosure and intellectual capital (IC) disclosure on firm value. The number of samples used in this research is 40 observation pharmaceutical companies listed on the Indonesia Stock Exchange. This research uses purposive sampling technique in accordance with predetermined criteria. The analysis technique used is panel data regression analysis with Eviews program. The results showed that ERM disclosure and IC disclosure had a positive and significant effect on firm value. Keywords: Enterprise Risk Management Disclosure; Intellectual Capital Disclosure; Firm Value; Covid-19.